Effects of Intraperitoneal Ozone Therapy in Cervicitis associated with Human Papillomavirus - Jaramillo Cazco, Peeter Francisco; Morales Fiallo, Daniel Adolfo; González Perdomo, Gregorina Del Carmen (Revista Universidad de Guayaquil, 2024)
Context: ozone therapy is a very effective therapeutic complement that can contribute to the symptoms of Cervicitis associated with the Human Papillomavirus. The general objective of this research is to assess the effects of intraperitoneal ozone therapy in the symptomatic and morphological picture of patients with Cervicitis associated with the Human Papillomavirus in Quito, Ecuador. Methods: is a Quasi-experimental research, whose methods are: hypothetical-deductive, systematization and clinical case study. Results: after 9 days of applying intraperitoneal ozone therapy, the patient showed absence of dysmenorrhea; and, at 22 days, favorable changes in the morphology of the cervix were evidenced, appreciating in Pet Scam inflammation of the cervix, reduction of inflammatory vascular congestion and reduction of "Schiller positive" lesion. It was determined that there is a correlation between the procedure of application of intraperitoneal ozone therapy with favorable symptomatic and morphological changes in patients with Cervicitis associated with the Human Papillomavirus, improving their quality of health. Conclusions: It was found that intraperitoneal ozone therapy applied to patients with Cervicitis associated with Human Papillomavirus improved the symptomatic and morphological picture of the patient.
Keywords: cervicitis; intraperitoneal; ozone therapy; Human Papillomavirus